Acute hemodynamic response of epicardial and endocardial cardiac resynchronization therapy, His bundle pacing and left bundle branch pacing. (24th May 2021) - Elliott, MK; Strocchi, M; Sidhu, BS; Mehta, V; Porter, B; Gould, J; Niederer, S; Rinaldi, CA
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Medtronic Background / Introduction Endocardial pacing and conduction system pacing are emerging as alternative methods to deliver cardiac resynchronization therapy (CRT) and have been shown to achieve superior acute hemodynamic response (AHR) compared to conventional epicardial pacing. However, a direct comparison of all the methods of delivering CRT has not yet been performed. Purpose: To directly compare the AHR of conventional CRT (BiV Epi), endocardial pacing (BiV Endo), His bundle pacing (HBP) and left bundle branch pacing (LBBP) during a temporary CRT study. Methods: 4 patients underwent a temporary CRT and hemodynamic study. Temporary pacing was achieved using quadripolar catheters in the right atrium and coronary sinus, and roving decapolar catheters in the right ventricle (RV) and left ventricle (LV) via retrograde aortic access. Hemodynamic assessment was performed with a PressureWire X (Abbott, CA, USA) in the LV cavity. AHR was calculated as the percentage improvement in LV dP/dtmax from baseline AAI or RV pacing (if underlying complete heart block). Results: The patients had a mean age of 67.5 ±5.8 years and all had non-ischemic cardiomyopathy with severe LV impairment (mean ejection fraction 22.5 ±7.4%). 3 patients had left bundle branch block and 1 patient had complete heart block with an RV paced rhythm (mean QRS duration 157 ±24 ms). All methods of delivering CRT achieved a mean AHR of >10%, which is considered clinically significant and is predictive of LV remodelling at 6 months. Mean AHR during BiV Epi pacing was 12.6 ±5.0%. There was a trend towards higher AHR for BiV Endo pacing (23.6 ±7.6%), HBP (17.4 ± 9.5%) and LBBP (16.1 ±7.8%) as shown in figure 1, however there was no significant difference between groups on one-way analysis of variance (p = 0.348). Conclusions: All methods of delivering CRT achieved an AHR >10%. The AHR during BiV Endo pacing, HBP and LBBP was higher than for BiV Epi pacing, but this did not reach statistical significance. Further investigation with larger studies is required to determine which method of delivering CRT achieves the best hemodynamic response. Figure 1. Box plot of acute hemodynamic response (AHR) for conventional cardiac resynchronization therapy (BiV Epi), endocardial pacing (BiV Endo), His bundle pacing (HBP) and left bundle branch pacing (LBBP). Data displayed as median (solid line), mean (+), 1st and 3rd quartiles (box) and minimum and maximum values (whiskers).